Pemberdayaan kelompok wanita tani (KWT) desa Teluk Empening kecamatan Terentang kabupaten Kubu Raya - Fenny Imelda; Ledy Purwandani; Yani Riyani (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2021)
Teluk Empening Village, located in Terentang District, Kubu Raya Regency, West Kalimantan Province, is a ginger-producing area. So far, ginger is only sold fresh and there has been no processing effort to extend its shelf life and increase its economic value. Ginger has strategic value because besides being used as a spice in the kitchen, it is also widely used in the health sector. This community partnership program aims to empower community groups in Teluk Empening Village who are classified as economically non-productive but have a strong desire to become entrepreneurs, namely the female farmer group (KWT). This program collaborates with KWT Silva Lestari as a partner, ginger as the main commodity cultivated by KWT is used as a strategic potential in this empowerment program. The methods used in order to achieve goals include: socialization in the form of delivery of information, transfer of knowledge and technology (science and technology) in the form of appropriate technology training (TTG) as a solution to partner problems as well as monitoring and evaluation and assistance regarding the sustainability of training results. Education about the potential of ginger is able to motivate and change the mindset of partners to be more creative in seeing opportunities for diversification of processed ginger. Simple administration and bookkeeping training can increase the knowledge and skills of partners in making simple bookkeeping for small businesses. The touch of science and technology in the form of TTG processing of ginger improves the skills of partners, where partners are able to process ginger into several processed healthy food products that have economic value, namely dry ginger, ginger powder / powder, dried ginger candy, powdered ginger (instant) and ginger syrup. The skills and knowledge obtained are used as partners as capital to start a small business by producing ginger syrup and dried candied ginger.